The Effect of The Leaf Diary Game on Increasing The Classification Ability of Children Aged 5-6 Years - Andina, Radhia; Wita, Arsyizahma; Razman, Rasyid (CV Berkah Syahdin Trust, 2025)
Purpose – This study aims to examine the effect of using a leaf diary as an educational medium on the classification abilities of children aged 5–6 years. Classification is a fundamental component in the development of early mathematical concepts and cognitive structuring in childhood.Design/methods/approach – The study employed a quantitative research approach with a pretest-posttest design. The research involved expert judgment for content validation and utilized the normalized N-Gain formula to analyze data collected from the classification activities of early learners before and after the intervention. The leaf diary, containing various types of leaves for observation and comparison, was implemented as a central medium during the learning sessions.Findings – The results demonstrated that the use of a leaf diary had a positive effect on the development of children’s classification abilities. The N-Gain analysis showed significant improvement in children's ability to categorize and group objects based on observable characteristics. This improvement is attributed to the engaging nature of the leaf diary, which provided children with tangible and relatable learning experiences through direct exploration and observation.Research implications/limitations – While the findings confirm the effectiveness of the leaf diary, the study was limited in scope to short-term outcomes and a single learning topic. Future research is recommended to assess its impact across different domains and with larger sample sizes, including longitudinal studies to measure retention and transfer of skills. Originality/value – This study highlights the pedagogical value of nature-based learning tools, such as the leaf diary, in fostering early classification skills. By connecting learning with the natural environment, the study provides educators with a practical and developmentally appropriate method to support foundational mathematical thinking in early childhood education.